Pre-reduction of United Manganese of Kalahari Ore in CO/CO2, H2/H2O, and H2 Atmospheres - Davies, J.; Tangstad, M.; Schanche, T. L.; du Preez, S. P. (Metallurgical and materials transactions. B, Process metallurgy and materials processing science, 2023)
The incorporation of hydrogen, which is a relatively unexplored reductant used during ferromanganese (FeMn) production, is an attractive approach to lessen atmospheric gaseous carbon release. The influence of hydrogen on the pre-reduction of carbonate-rich United Manganese of Kalahari (UMK) ore from South Africa was investigated. Experiments were performed in 70 pct CO 30 pct CO 2 (reference), 70 pct H 2 30 pct H 2 O, and 100 pct H 2 gas atmospheres at 700 °C, 800 °C, and 900 °C. Calculated phase stability diagrams and experimental results showed good correlation. The pre-reduction process involved two reactions proceeding in parallel, i.e ., the pre-reduction of higher oxides and the decomposition of carbonates present in the ore. A thermogravimetric (TG) furnace was employed for the pre-reduction of the ore in various atmospheres. The calculated weight loss percentage was used to determine the degree and rate of pre-reduction. It was found that the oxidation state of higher Fe- and Mn-oxides was lowered when treated in 70 pct H 2 30 pct H 2 O and 70 pct CO 30 pct CO 2 , whereas FeO was metalized when using 100 pct H 2 . As for the intrinsic carbonates, the majority thereof were decomposed in the CO/CO 2 atmosphere at 900 °C, and ≥ 700 °C in the H 2 /H 2 O and H 2 atmospheres. Additionally, the degree and rate of reduction were accelerated by increasing the pre-reduction temperature and by employing a hydrogen-containing gas atmosphere (70 pct H 2 30 pct H 2 O, and 100 pct H 2 ). Scanning electron microscopy and electron microprobe analysis revealed the presence of three phases in the pre-reduced ore: (i) Mn- and Fe-rich, (ii) Mg- and Ca-rich, and (iii) Mg-, Si-, K-, and Na-rich. It was also found that there were no appreciable differences in porosity and decrepitation of the ores treated in the CO/CO 2 and hydrogen-containing atmospheres. The use of a hydrogen atmosphere showed potential for the pre-reduction of carbonate-containing manganese ores as it accelerated the decomposition of the carbonates as well as facilitated the metallization of Fe-oxides present in the ore.